Qualities of full-cream powdered milk of different brands available in retail markets of Bangladesh (Bangladesh Journal of Animal Science, 2013)
The present experiment was conducted to evaluate the physical and microbiological qualities of whole powdered milk of six different brands (Kwality, NIDO, Diploma, Anchor, Farmland and Starship) available in retail market at Mymensingh town. Each brand was considered as treatment and three samples (replications) were taken for each brand. For this purpose, powdered milk samples were collected and analyzed to know the physical parameters mainly color, flavor, taste, solubility, appearance and specific gravity, and microbiological qualities such as total viable bacterial count and coliform count. In case of physical quality, all the six brands possessed the good quality grade and no significant difference was observed except that of specific gravity which varied significantly among the brands. Specific gravity was almost similar to the normal cow milk when the dried milk was reconstituted. Significant variations (p